The Influence Of Electronic Word Of Mouth And Brand Image On Purchasing Decisions; The Role Of Brand Trust As A Mediation Variable (Study of Xiaomi Brand Smartphone Users in Dobo City, Aru Islands Regency) - Benamen, Hempry Arnold Samuel; Huwae, Victor Ernest; Saptenno, Sammy (Jurnal Ekonomi, 2024)
The purpose of this research is to determine the role of brand trust as a mediating variable in the influence of electronic word of mouth variables and brand image variables on purchasing decision variables. This research is included in quantitative research. The type of data in this research is quantitative data and the data source uses primary data. The population in this study were all Xiaomi brand smartphone users in Dobo City, Aru Islands Regency. The sampling method used was non-probability sampling using purposive sampling technique. The data analysis method uses Partial Least Square (PLS) and the data is processed using SmartPLS software version 3.3.3. The research results show that electronic word of mouth has a positive and significant effect on brand trust, brand image has a positive and significant effect on brand trust, brand trust has a positive and significant effect on purchasing decisions, electronic word of mouth has a positive and significant effect on purchasing decisions through brand trust as a mediating variable, brand image has a positive and significant effect on purchasing decisions through brand trust as a mediating variable.